Enhancing pest detection in deep learning through a systematic image quality assessment and preprocessing framework - Jia, Shuyi; Horri Rezaei, Maryam; Honarvar Shakibaei Asli, Barmak (MDPI, 2025)
This study addresses the critical challenge of variable image quality in deep learning-based automated pest identification. We propose a holistic pipeline that integrates systematic Image Quality Assessment (IQA) with tailored preprocessing to enhance the performance of a YOLOv5 object detection model. The methodology begins with a No-Reference IQA using BRISQUE, PIQE, and NIQE metrics to quantitatively diagnose image clarity, noise, and distortion. Based on this assessment, a tailored preprocessing stage employing six different filters (Wiener, Lucy–Richardson, etc.) is applied to rectify degradations. Enhanced images are then used to train a YOLOv5 model for detecting four common pest species. Experimental results demonstrate that our IQA-anchored pipeline significantly improves image quality, with average BRISQUE and PIQE scores reducing from 40.78 to 25.42 and 34.94 to 30.38, respectively. Consequently, the detection confidence for challenging pests increased, for instance, from 0.27 to 0.44 for Peach Borer after dataset enhancement. This work concludes that a methodical approach to image quality management is not an optional step but a critical prerequisite that directly dictates the performance ceiling of automated deep learning systems in agriculture, offering a reusable blueprint for robust visual recognition tasks.
The original image data presented in this study are openly available in the IP102 dataset at https://www.kaggle.com/datasets/rtlmhjbn/ip02-dataset (accessed on 20 July 2025).
Keywords: 46 Information and Computing Sciences; 40 Engineering; 4603 Computer Vision and Multimedia Computation; Machine Learning and Artificial Intelligence; Networking and Information Technology R&D (NITRD); automated pest identification; deep learning; image preprocessing; image quality assessment; convolutional neural networks; YOLOv5; computer vision